2015
DOI: 10.1108/aaaj-01-2015-1932
|View full text |Cite
|
Sign up to set email alerts
|

Annexing new audit spaces: challenges and adaptations

Abstract: Access to this document was granted through an Emerald subscription provided by emerald-srm:123705 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(58 citation statements)
references
References 125 publications
(192 reference statements)
0
57
0
1
Order By: Relevance
“…However, research suggests that in the 1980s the audit profession underwent a gradual cultural shift from a legitimate public service to a more commercially driven emphasis (e.g., Hanlon ; Wyatt ; Carnegie and Napier ; Malsch and Gendron ; Picard et al ). Some studies suggest that characteristics of firms (e.g., firm size and hierarchy, Goetz et al ; commercialistic values, Wyatt , Suddaby et al , Carter and Spence , Spence and Carter ; expansion into “new audit spaces” outside of the traditional attest audit domain, Andon et al ) coupled with characteristics of partners (e.g., shifting from disciplined and dedicated professional to one with an entrepreneurial bent, Greenwood and Suddaby , Gendron and Spira , Kornberger et al ; diluted job autonomy, Bamber and Iyer , Lupu and Empson ) within a self‐regulating system were at fault. Despite the perception that internal quality review (IQR) and peer‐review processes (i.e., self‐regulation) were effective at monitoring the profession (e.g., Anantharaman ; Houston and Stefaniak ) and were in some instances beneficial (e.g., Hilary and Lennox ; Casterella et al ), the avalanche of audit failures during the early 2000s lends credibility to the accusation that commercialism got the best of firms, resulting in reduced confidence in the audit profession.…”
Section: Introductionmentioning
confidence: 99%
“…However, research suggests that in the 1980s the audit profession underwent a gradual cultural shift from a legitimate public service to a more commercially driven emphasis (e.g., Hanlon ; Wyatt ; Carnegie and Napier ; Malsch and Gendron ; Picard et al ). Some studies suggest that characteristics of firms (e.g., firm size and hierarchy, Goetz et al ; commercialistic values, Wyatt , Suddaby et al , Carter and Spence , Spence and Carter ; expansion into “new audit spaces” outside of the traditional attest audit domain, Andon et al ) coupled with characteristics of partners (e.g., shifting from disciplined and dedicated professional to one with an entrepreneurial bent, Greenwood and Suddaby , Gendron and Spira , Kornberger et al ; diluted job autonomy, Bamber and Iyer , Lupu and Empson ) within a self‐regulating system were at fault. Despite the perception that internal quality review (IQR) and peer‐review processes (i.e., self‐regulation) were effective at monitoring the profession (e.g., Anantharaman ; Houston and Stefaniak ) and were in some instances beneficial (e.g., Hilary and Lennox ; Casterella et al ), the avalanche of audit failures during the early 2000s lends credibility to the accusation that commercialism got the best of firms, resulting in reduced confidence in the audit profession.…”
Section: Introductionmentioning
confidence: 99%
“…Following this analysis of the evolving new audit space of regulatory work, it is helpful to consider the extent to which it shares common themes across new audit spaces as identified by Andon et al (2015). In their review of new audit spaces, Andon et al (2015Andon et al ( , pp. 1404Andon et al ( -1416 identified four themes -independence, reporting, accreditation and institutionalised cultural capital, and reorientations in the mediating roles of auditing.…”
Section: Discussionmentioning
confidence: 99%
“…Their motivation was to acknowledge the increase in auditing and assurance of information published in a variety of new spaces and to respond to calls to undertake more detailed empirical work on the extension of audit-type practices into new spaces. Subsequently, in a special issue on 'Contemporary Professional Work: Accounting and Beyond' in this journal, Andon et al (2015) undertook a wider review of the emergence of new audit spaces. They identified new audit spaces as including efficiency and value for money auditing (Radcliffe, 1998;1999), performance auditing (Gendron et al, 2007), sustainability assurance (O'Dwyer, 2011;O'Dwyer et al, 2011), salary cap auditing (Andon and Free, 2012;2014), e-commerce assurance (Barrett and Gendron, 2006;Gendron and Barrett, 2004), and rankings and ratings (Jeacle and Carter, 2011) (see summary Andon et al, 2015Andon et al, , p. 1408.…”
Section: Regulatory Space New Audit Spaces and Regulatory Workmentioning
confidence: 99%
See 2 more Smart Citations